Classical logic and schizophrenia: por a neutral game semantics - Redmond, Juan; Lopez-Orellana, Rodrigo (Revista de Filosofía, 2018)
In this paper we draw a proposal to develop a logic of fictions in the game-theoretical approach of dialogical pragmatism. From one of the main criticisms that point to classical logic: the structural schizophrenia of its semantics (Lambert, 2004: 142-143; 160), we review the ontological commitments of the two main traditions of logic (Aristotle and Frege) to highlight their limits concerning the analysis of fictional discourse, and the overcoming from a pragmatic game perspective.